Hospital microbiome: unspoken role in healthcare-associated infections - Al-Wethainani, Rawan Mohammed; Zakariah, Siti Zulaikha; Jasni, Azmiza Syawani; Ibrahim, Rosni; Tengku Jamal-ud-Din, Tengku Zetty Maztura (Pakistan Medical Association, 2023)
Infections obtained in a healthcare or hospital setting are known as nosocomial illnesses or hospital-acquired infections (HAIs). Despite their role as healing environments, hospitals are home to a diverse range of bacteria, and it is widely assumed that the hospital microbiome changes as the facilities are used. The increased use of broad-spectrum antibiotics to treat bacterial infections has resulted in the increasing incidence of nosocomial infections. HAI is caused mostly by bacteria such as Acinetobacter baumannii, Klebsiella pneumoniae, Escherichia coli, Enterococci spp., Methicillin-resistant Staphylococcus aureus (MRSA), and others. Understanding the nature of bacterial communities in hospital environments is essential for tracking the transmission of antibiotic resistance genes. The efforts of medical organizations and hospitals are significant in promoting awareness and providing training. The results of bacterial diversity studies related to patients, staff, and surfaces of the newly established centers are reviewed and presented in this study.